The Study of Random Fields of Stress in Pure Shear Stochastically Inhomogeneous Half-Plane under Creep - M. A. Yashin; N. N. Popov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2010)
We studied the solution of a nonlinear boundary value problem of the steady-state creep at pure shear of a stochastically non-uniform half-plane. The solution of the problem is searched in correlation approximation on the basis of a spectral representation of random function method. On the basis of the received solution the statistical analysis of stress field near to half-plane boundary is carried out. It is shown, that in an interface dispensing of stress much more, than for deep layers.